2016
DOI: 10.21836/pem20160410
|View full text |Cite
|
Sign up to set email alerts
|

Oral supplementation of magnesium aspartate hydrochloride in horses with Equine Metabolic Syndrome

Abstract: Diabetes mellitus type 2 is a worldwide problem in human medicine as is the equine equivalent "Equine Metabolic Syndrome" (EMS). In humans, an inverse relationship between serum magnesium content and the incidence of diabetes mellitus type II has been shown. Humans with peripheral insulin resistance often show cellular magnesium deficits and multiple studies have demonstrated the beneficial effect of dietary magnesium supplementation on insulin sensitivity. One study has evaluated the effects of magnesium supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…It has a positive influence on different parameters related to the control of blood glucose concentration and counteracts the development of an insulin resistance (Günther, ; Volpe, ). In EMS patients, similar tendencies have been shown (Winter, Liertz, Merle, Aschenbach, & Gehlen, ). In human patients with diabetes mellitus type 2, an increase in [Mg 2+ ] i from 0.43 ± 0.06 mmol/L to 0.61 ± 0.06 mmol/L was achieved by oral magnesium supplementation.…”
Section: Introductionsupporting
confidence: 73%
“…It has a positive influence on different parameters related to the control of blood glucose concentration and counteracts the development of an insulin resistance (Günther, ; Volpe, ). In EMS patients, similar tendencies have been shown (Winter, Liertz, Merle, Aschenbach, & Gehlen, ). In human patients with diabetes mellitus type 2, an increase in [Mg 2+ ] i from 0.43 ± 0.06 mmol/L to 0.61 ± 0.06 mmol/L was achieved by oral magnesium supplementation.…”
Section: Introductionsupporting
confidence: 73%
“…The use of dietary supplements to facilitate BM losses or to improve ID is popular, but their efficacy remains questionable or unproven. Supplements including magnesium, chromium, and short‐chain fructo‐oligosaccharides have received support based on some evidence of improved insulin regulation, although other studies have not confirmed these positive effects . Little benefit has been shown for other supplements including cinnamon, l ‐carnitine, and Psyllium, although some promising effects are reported for a feed enriched with Spirulina platensis algae and the wheat bran protein aleurone…”
Section: Managementmentioning
confidence: 99%
“…No differences were found in the blood levels of glucose and insulin immunoreactivity or in the insulin sensitivity of peripheral tissues (Chameroy et al 2011). Another study showed improvements in the CGIT (shorter positive phase duration of the glucose curve) in 3/5 horses and a trend for a lower fructosamine concentration after three months of supplementation with 30 mg/kg magnesium as magnesium-aspartate hydrochloride (Winter et al 2016). Because of the small sample size and limited repeatability of the glucose curve, results of the latter study should be interpreted with care.…”
Section: Discussionmentioning
confidence: 98%